Brief interventions 2.0: a new agenda for alcohol policy, practice and research - Duncan Stewart; Mary Madden; Jim McCambridge (BMC, 2024)
Abstract Background Alcohol problems are increasing across the world and becoming more complex. Limitations to international evidence and practice mean that the screening and brief intervention paradigm forged in the 1980s is no longer fit for the purpose of informing how conversations about alcohol should take place in healthcare and other services. A new paradigm for brief interventions has been called for. Brief interventions 2.0 We must start with a re-appraisal of the roles of alcohol in society now and the damage it does to individual and population health. Industry marketing and older unresolved ideas about alcohol continue to impede honest and thoughtful conversations and perpetuate stigma, stereotypes, and outright fictions. This makes it harder to think about and talk about how alcohol affects health, well-being, and other aspects of life, and how we as a society should respond. To progress, brief interventions should not be restricted only to the self-regulation of one's own drinking. Content can be orientated to the properties of the drug itself and the overlooked problems it causes, the policy issues and the politics of a powerful globalised industry. This entails challenging and reframing stigmatising notions of alcohol problems, and incorporating wider alcohol policy measures and issues that are relevant to how people think about their own and others' drinking. We draw on recent empirical work to examine the implications of this agenda for practitioners and for changing the public conversation on alcohol. Conclusion Against a backdrop of continued financial pressures on health service delivery, this analysis provokes debate and invites new thinking on alcohol. We suggest that the case for advancing brief interventions version 2.0 is both compelling and urgent.